2022
DOI: 10.3390/cancers14205056
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Macropinocytosis Contributes to Malignant Progression: A Review of Recent Evidence in Endometrioid Endometrial Cancer Cells

Abstract: Macropinocytosis is an essential mechanism for the non-specific uptake of extracellular fluids and solutes. In recent years, additional functions have been identified in macropinocytosis, such as the intracellular introduction pathway of drugs, bacterial and viral infection pathways, and nutritional supplement pathway of cancer cells. However, little is known about the changes in cell function after macropinocytosis. Recently, it has been reported that macropinocytosis is essential for endometrial cancer cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 138 publications
0
3
0
Order By: Relevance
“…In addition, modifying the MV surface membrane with functional peptides for controlling macropinocytosis induction is considered to help develop the MV-based intracellular delivery of therapeutic/diagnostic molecules. Macropinocytosis pathways are significantly enhanced by cancer-related receptors such as EGFR and CXCR4, and oncogenic K-Ras expression, for attaining the efficient cellular uptake of nutrition from outside the cells. A pancreatic cancer model in vivo has previously demonstrated strongly decreased cancer progression following treatment with macropinocytosis inhibitor . These findings inspired the development of exosome-based in vivo delivery of nucleic acids into oncogenic K-Ras-expressing pancreatic tumors, which significantly reduced cancer proliferation .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, modifying the MV surface membrane with functional peptides for controlling macropinocytosis induction is considered to help develop the MV-based intracellular delivery of therapeutic/diagnostic molecules. Macropinocytosis pathways are significantly enhanced by cancer-related receptors such as EGFR and CXCR4, and oncogenic K-Ras expression, for attaining the efficient cellular uptake of nutrition from outside the cells. A pancreatic cancer model in vivo has previously demonstrated strongly decreased cancer progression following treatment with macropinocytosis inhibitor . These findings inspired the development of exosome-based in vivo delivery of nucleic acids into oncogenic K-Ras-expressing pancreatic tumors, which significantly reduced cancer proliferation .…”
Section: Discussionmentioning
confidence: 99%
“…Active macropinocytotic cellular uptake was recently noted by us to play crucial roles for secreted exosomes. ,, Macropinocytosis is a clathrin-independent and actin-dependent endocytosis pathway, including actin rearrangements, lamellipodia formations, plasma membrane ruffling, and engulfment of large fluid volumes (>1 μm in diameter) outside cells. Macropinocytosis has been shown to be stimulated by the activation of specific receptors, such as the epidermal growth factor receptor (EGFR) and C–X–C chemokine receptor type 4 (CXCR4). The expression of oncogenic K-Ras protein has also been shown to influence macropinocytosis, causing malignant progression. A previous study conducted by us has demonstrated a significantly increased cellular uptake of exosomes via EGFR (e.g., 27-fold increased uptake of exosomes by EGFR activation with 500 nM EGF ligand for 24 h) in human epidermoid carcinoma cells (A431) caused by macropinocytosis induction. Oncogenic K-Ras expression (K-Ras G12C allele) in human pancreatic adenocarcinoma cells (MIA PaCa-2) also demonstrated high efficacy for cellular exosome uptake .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation